2015
DOI: 10.4238/2015.june.26.12
|View full text |Cite
|
Sign up to set email alerts
|

Regulating effects of insertion direction of matrix attachment regions on transgenic expression in stably transformed Chinese hamster ovary cells

Abstract: ABSTRACT. We investigated the effects of different directions of insertion of matrix attachment region (MAR) sequences on transgenic expression in stably transformed Chinese hamster ovary (CHO) cells. The MAR sequences were inserted in forward or reverse directions into the expression vectors, and transfected into CHO cells. The expression of the chloramphenicol acetyltransferase (CAT) reporter gene and the relative copy numbers of the CAT gene were analyzed. The CAT gene expression levels in the vector with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, S/MARs can also reduce variations in transgene expression among different cells to some extent, and the rate of transgene genomic integration can be increased . However, some reports have shown that S/MARs have inconsistent effects on transgene expression .…”
mentioning
confidence: 99%
“…In addition, S/MARs can also reduce variations in transgene expression among different cells to some extent, and the rate of transgene genomic integration can be increased . However, some reports have shown that S/MARs have inconsistent effects on transgene expression .…”
mentioning
confidence: 99%